Postcolonial Trauma, Memory and Care in Bodunrin B. Sasore’s Breath of Life - Isiguzo, Chikwurah Destiny (Research in African literatures, 2025)
New Nollywood is offering aesthetically driven strategies of reading the African colonial past and its traumatic and complex implication in the postcolonial present and future. Postcolonial film has become a mode of memorializing the paradigm-shattering colonial experience and its persistent legacy on individuals and communities. The present study therefore explicates how B. B. Sasore’s film, Breath of Life (2023), rethinks and reimagines colonial experience and impact by focusing on the traumatic experience of individual and collective victims of colonial violence. Following conceptualizations of trauma, memory, and care, this study examines how Breath of Life (2023), through the depiction of memory, connects a traumatic colonial past to the present. The study argues that care can mollify traumatic individual and collective experiences.